2013
DOI: 10.4028/www.scientific.net/amm.421.663
|View full text |Cite
|
Sign up to set email alerts
|

Optical 3D Scanning of Cutting Tools

Abstract: The paper shortly illustrates the general concept of Reverse Engineering, which includesalso the 3D scanning. In the main part of the paper the concrete 3D scanning process of chosen individual objects are described. The problems that occurred during 3D digitizing of individual parts are step by step discussed and solved. The paper deals with 3D scanning of ball nose end mills and screw drill. The article gives a procedure for digitizing and comparing the results of the scanned digital models of the two ball n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This was measurement on 3D scanner with optical devises. The measurements of the specimens were performed in the same way they are presented by other authors [8,9]. In this figure it can be observed that it is a big variation of the thickness, between 1.46 mm and 1.58 mm.…”
Section: Experimental Determinations Of Materials Parametersmentioning
confidence: 84%
“…This was measurement on 3D scanner with optical devises. The measurements of the specimens were performed in the same way they are presented by other authors [8,9]. In this figure it can be observed that it is a big variation of the thickness, between 1.46 mm and 1.58 mm.…”
Section: Experimental Determinations Of Materials Parametersmentioning
confidence: 84%
“…It has also been utilized for medical engineering purposes, where body structures were scanned for assessment and, in some cases, replication purposes [32]. Objects have been scanned for reverse engineering purposes [33,34], quality assurance [35], creating object repositories (e.g., [36]), preserving historical artifacts [37] and assessing turbine blades [38] and concrete slabs [6].…”
Section: Three-dimensional Scanning and Its Application Areasmentioning
confidence: 99%
“…SECO DNMG150604L-UX cutting tool was used in cutting experiment. Cutting tool simulation model geometry is the exactly same shape as experimental cutting insert and model is prepared in CAD system utilizing 3D scan and reverse engineering [12,13]. Although the tool is set up as a rigid, it can be done by a thermal analysis of tool, the model of tool is meshed using 3D tetrahedron elements.…”
Section: D Fem Model Of Turningmentioning
confidence: 99%